Becoming and Belonging in Ireland 1200-1600 AD : Essays on Identity and Cultural Practice (Book collections on Project MUSE., 2018)
The period c. 1200-1600 was marked by the achievements and decline of the Anglo-Norman colony in Ireland, refashioning of Gaelic elite identity, Reformation, and reassertion of English control that led to Plantation projects, bringing new people and ideas to the island. This collection explores the complexities and predicaments of identity, and the cultural practices used to express and underpin them in this key period, ranging from the micro-scale and personal to the macro-scale emergence of ideas of national identity. Divided into two interrelated parts, 'predicaments of identity' and 'negotiating cultural practices', it presents and discusses people, their places and materials, from Anglo-Norman and Old English, Gaelic, New English and hybridised cultural backgrounds. The authors consider the extent to which there was a relational character to identities in Ireland, whereby senses of being were constructed through engagements with others, and how the power of the past, in both framing and providing stability for identity formulations, is explicit in the ways in which groups intentionally evoked their own histories and connections to place, to reaffirm and bolster identity and solidarity. Cultural practices could become naturalised through repetition and, as reflections of identity, they were formed, transformed or abandoned when necessary or expedient.